DCA RI-Singapura: Tinjauan Negosiasi - Yusuf Hamdan (MediaTor (Jurnal Komunikasi), 2008)
Planning is a crucial stage which could determine and leverage activities’ success. There are many approach to build a plan to implement activities. This article explores BATNA Methods (Best Alternative to Negotiate Agreement) as an approach based on negotiation plan. Providing the Case of Indonesian-Singapore Defense Cooperation Agreement as case being studied, it was concluded that the lack of BATNA has contribute a loss for Indonesia. More concessions were given to Singapore by Indonesian in that agreement,and caused a potential disadvantage for RI government.